Capturing Psuedo-Innovation in ELT: The Analysis of implementing Differentiated Learning to suburban Private Madrasahs - Muhammad Sandy Al Fath; Putri, Nikmah Sistia Eka (Universitas Ahmad Dahlan, 2024)
The implementation of differentiated learning in private madrasahs raises a big question mark regarding the suitability between theory and practice in the field. The principle of differentiated learning, which is claimed to accommodate diversity, turns out to be far different when implemented, especially in private madrasahs that are transitioning from the previous curriculum. The main purpose of this research is to explore the illusory construction of innovation in differentiated English learning that results in pseudo-innovation. The approach used is a qualitative approach with the type of ethnography. The research was conducted in 4 private madrasahs in the suburbs of Sampit city. The research subjects were English teachers who implemented differentiated learning in the four madrasas. The stage analysis process was assisted by the theory of innovation-decision process by Everett Rogers. The results of this study show that (1) the illusion of innovation in differentiated English learning occurs because the stages of the innovation diffusion decision process cause anomalies in the process. (2) Madrasahs are forced to follow the decision of the Ministry of Religious Affairs which requires the implementation of an independent curriculum including differentiated learning which results in madrasahs being trapped in pseudo-innovation. (3) Madrasahs are registered as institutions that implement differentiated learning. However, in practice, madrasahs still adopt old learning and ignore innovations because they are not considered to be following the characteristics of the madrasah itself. (4) this research implies that it will be an evaluation material for the Ministry of Religious Affairs to pay more attention to private madrasahs in implementing differentiated learning. (5) Confirming pseudo-innovation